2017
DOI: 10.1111/jfpe.12664
|View full text |Cite
|
Sign up to set email alerts
|

Shelf‐life prediction of microencapsulated Β‐galactosidase powder prepared using enteric double‐coating technology

Abstract: In this study, we estimated the storage period of enteric double‐microencapsulated lactase (β‐d‐galactosidase) powder used to address lactose intolerance associated with milk. The coating materials were medium‐chain triglyceride for the primary coating, and hydroxypropyl methylcellulose phthalate (HPMCP) and shellac for the secondary enteric coating. The isotherm profiles of the lactase microcapsule powders coated with HPMCP and shellac were type II and III, respectively. Compared with the shellac‐coated micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…These advantages promoted the sustained drug release properties of the pellets in the gastrointestinal tract, as shown in Figure B. Moreover, shellac coating can also be used as a secondary enteric coating for lactase (β-galactosidase) microcapsules. , In another study, sodium butyrate tablets with a precoating of HPMC and external coating of shellac were developed and optimized in in vitro experiments. The tablets could release sodium butyrate with variable intestinal transit times in the ileocecal regions and colons of healthy subjects and patients with Crohn’s disease, thereby exhibiting therapeutic value in patients with inflammatory bowel disease …”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%
“…These advantages promoted the sustained drug release properties of the pellets in the gastrointestinal tract, as shown in Figure B. Moreover, shellac coating can also be used as a secondary enteric coating for lactase (β-galactosidase) microcapsules. , In another study, sodium butyrate tablets with a precoating of HPMC and external coating of shellac were developed and optimized in in vitro experiments. The tablets could release sodium butyrate with variable intestinal transit times in the ileocecal regions and colons of healthy subjects and patients with Crohn’s disease, thereby exhibiting therapeutic value in patients with inflammatory bowel disease …”
Section: Shellac-based Delivery Systemsmentioning
confidence: 99%
“…Preparation of the secondary enteric coating material followed the method of Ahn et al (2018b). In brief, the secondary enteric coating materials being tested, HPMCP and shellac, were each dissolved in 80 mL of distilled water, where the pH was adjusted to 8.0 with 0.1 N sodium hydroxide.…”
Section: Microencapsulation Of Lactase: Emulsion Preparationmentioning
confidence: 99%
“…A powder of lactase microcapsules coated with enteric material might address this problem. In one study, it was demonstrated that enteric-coated lactase microcapsules have good physicochemical properties and stability (Ahn et al, 2018b). No toxicity of hydroxypropyl methylcellulose phthalate (HPMCP) has been observed in toxicological tests, and it has been widely used as an enteric coating material (Kitagawa et al, 1970;Ito and Toida, 1972;Rowe et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The absolute value of the activation energy of samples containing cacao nibs extract was higher than that of control. Ahn et al (2018) reported that a high absolute value for the activation energy corresponds to a longer storage period.…”
Section: Determination Of Shelf-lifementioning
confidence: 99%